Globalization of the Stock Market is Important in Developing Diversification Opportunities for Global Institutional Investors in New Uzbekistan - Kamilova Sevara Anvarovna (Zien Journals, 2023)
In recent years, New Uzbekistan has emerged as a vibrant and promising destination for global institutional investors seeking diversification opportunities. This newfound interest is largely driven by the globalization of the stock market in the country, which has opened doors to new possibilities and avenues for international investors looking to expand their portfolios and manage risks efficiently. The journey of New Uzbekistan's stock market towards globalization has been marked by transformative reforms, economic liberalization, and progressive policies. This article explores the importance of the globalization of the stock market in developing diversification opportunities for global institutional investors in New Uzbekistan
Keywords: globalization; stock market; new Uzbekistan